The Gambia : 2015 Article IV Consultation-Press release; Staff Report; and Statement by the Executive Director for the Gambia. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that The Gambia has experienced large balance of payments and fiscal imbalances, caused by persistent policy slippages in recent years and financial difficulties in public enterprises. The IMF supported the authorities' efforts through a Rapid Credit Facility (RCF) disbursement in early April 2015 and a Staff-Monitored Program (SMP). However, major policy slippages have occurred since the RCF disbursement, pushing the SMP off track and worsening the outlook considerably. In light of the elevated level of public debt, the government should prioritize infrastructure investments that help address poverty and improve the business environment. The authorities are encouraged to continue their efforts to improve supervision capacity to enhance financial stability.